Temporal work stressors and satisfaction with work, life and health among health professionals in Switzerland (Swiss Medical Weekly, 2020)
BACKGROUND Working in a hospital can be both rewarding and stressful. Whether one or the other is dominant depends on a number of factors ranging from shift work, physical demands, responsibilities and time pressure to job autonomy, work climate and leisure time. AIM This study aimed to examine associations between temporal work stressors and satisfaction with work, life and health among health professionals in general, and nurses and physicians in particular. Associations were further investigated for possible mediating and intervening factors. METHODS Cross-sectional survey data on 1232 health professionals at three public hospitals and two rehabilitation clinics were collected in 2015/2016. Stepwise multiple linear regression analyses were used to estimate the standardised effects (beta coefficients) of temporal work stressors (overtime and time pressure), and organisational and personal resources (job autonomy, work climate, internal control belief) on general stress as the assumed mediator and finally on satisfaction with work, life and health. RESULTS Temporal work stressors were found to strongly predict general stress symptoms among health professionals (β = 0.25) and particularly physicians (β = 0.30), independently of the observed stress-buffering effects of organisational resources such as job autonomy (β = −0.09) or work climate (β = −0.22). Associations between temporal work stressors (as predictors) and satisfaction with work, life and health (as outcomes) turned out to be mostly indirect, mediated by general stress. General stress in turn was observed to be the strongest predictor of domain-specific satisfaction (β = −0.17 to −0.34), sometimes only surpassed by resources such as work climate or internal control belief. Explained variance of the three satisfaction outcomes in the fully specified regression or explanatory models ranged between 14% and 45% depending on the (sub-)sample (nurses, physicians, all health professionals) or the outcome. Control belief was revealed to be a strong and independent personal resource, particularly regarding satisfaction with life and health in general (β = 0.25/0.21). CONCLUSION Satisfaction and well-being of health professionals are strongly affected by job stressors such as frequent or excessive overtime work or permanent time pressure at work. Negative consequences of temporal work stressors are attenuated by organisational and personal resources such as a high level of job autonomy, a good work climate or a strong internal control belief.